The Reality Of Adopting Distance Education In Algerian Universities To Activate Digital Transformation - Belhamissi, Kheira Ouahiba; Tlemsani, Fatima (جامعة الوادي - University of Eloued, 2023)
The current study aims to know the reality of Algeria's adoption of distance education in the light of digital transformation from the point of view of both university teachers and students. We followed the descriptive approach with building two measurement tools and verifying their psychometric characteristics.they were applied to sample of (40) teachers from technical and literary disciplines and (45) students The results of the study show a high percentage of the importance of distance education, estimated at (57.14℅), as well as manifestations of its use by teachers, at a rate estimated at (100℅), which reflects their awareness of this type of education , With the presence of statistically significant differences in the averages of teachers' attitudes towards distance education due to the variable of specialization in favor of literary specialization, and the absence of differences in the attitudes of teachers towards distance education according to the variable of seniority. As for the challenges and problems facing Algerian students, they were expressed by (53.84℅), which Medium percentage, and we found significant differences between the attitudes of teachers and students towards distance education. Our study came out with a set of suggestions and recommendations.
مقال
Keywords: distance education ; digital transformation ; trends